Laser diffraction from capillary waves on liquid film surfaces - 朱峰 王宏 陈利菊 张建航 (Optoelectronics letters, 2013)
A simple experiment for laser diffraction of capillary waves on liquid film surface （LFS） is realized, Steaay ana wslul diffraction patterns are obtained. The dispersion relation of capillary waves on LFS is verified by laser diffraction. In particular, both the relation between the wave number and the film thickness at a fixed angular frequency and the relation between the angular frequency and the wave number at a fixed film thickness are investigated. The theoretical and experi- mental results are in good ageement.